Adsorption of cationized xylans onto polyethylene terephthalate fabrics for antimicrobial medical textiles. Issue 4 (February 2019) - Velkova, Nena; Zemljic, Lidija Fras; Saake, Bodo; Strnad, Simona
The main aim of this research was development of thin functional xylan layers on polyethylene terephthalate (PET) fabric surfaces. Xylans, derived from hard wood and oat spelt, were modified chemically in order to introduce cationic functional groups. Cationization of xylans was proved by elemental analysis, total bound nitrogen determination, and Raman techniques, as well as by polyelectrolyte titrations. The antimicrobial activity of xylans was investigated by the determination of Minimal Inhibitory Concentration against bacteria S. aureus and E. coli, and fungi C. albicans . Xylan solutions were then applied onto PET fabric using the spray coating technique. Charging behavior of the treated PET fabric samples was evaluated by potentiometric titration supported by X-ray electron spectroscopy. Hydrophilicity was examined by the water contact angle determination. The morphology of coated fabrics was analyzed using Scanning Electron Microscopy. The results of microbial testing showed that PET fabrics functionalized by cationic xylans act antimicrobially against S. aureus and E. coli . The presented work suggests that cationized xylans, originally derived from hard wood and/or oat spelt, could be applied successfully as a coating material for PET fabrics in order to introduce hydrophilicity and antimicrobial properties.